2004
DOI: 10.1021/jp049044a
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Cellooligosaccharides in Aqueous Solution from Molecular Dynamics Simulation:  Comparison of Cellotetraose, Cellopentaose, and Cellohexaose

Abstract: A molecular dynamics (MD) simulation was carried out for aqueous solutions of cellooligosaccharides to investigate their interactive behavior. Single and double strands of cellotetraose, cellopentaose, and cellohexaose were simulated in systems with TIP3P water. The cellotetraose double strand separated into two within 1 ns calculation time. An aggregation state of a cellohexaose double strand is firmer than that of cellopentaose in the simulation, supporting experimental results. The self-diffusional motion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The assumption that cellulose chains are essentially flexible coils in solution appears to be incorrect, since both this present MD simulation, as well as others, 36,37 have suggested that the chain actually exists primarily in a single extended, twisted conformation even in solution. This rigidity reduces the supposed configurational entropy that would favor solvation over crystal packing if the chains were writhing random coils, although the solvated chains would still have greater rotational and translational freedom than in the crystal.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The assumption that cellulose chains are essentially flexible coils in solution appears to be incorrect, since both this present MD simulation, as well as others, 36,37 have suggested that the chain actually exists primarily in a single extended, twisted conformation even in solution. This rigidity reduces the supposed configurational entropy that would favor solvation over crystal packing if the chains were writhing random coils, although the solvated chains would still have greater rotational and translational freedom than in the crystal.…”
Section: Discussionmentioning
confidence: 53%
“…8) such as has been seen in other MD simulations of cellooligomers using different force fields. 36 This twist resulted when the / angles went from À98.5°to approximately À75°, and w went from À142.3°to approximately À124°. After this initial conformational change, however, the chain was quite rigid, as was also observed in previous simulations of cellooligomers.…”
Section: The Origin Of the Barriers Exhibited In The Curves For Dp 2-mentioning
confidence: 99%
See 1 more Smart Citation
“…121 Finally, the H-bond observed for C was reported in a number of previous experimental and theoretical studies. 95,111,112,120,127,128,145,221,222 In the present simulations, this specific H-bond is the one with the highest occurrence (nearly 80%). It is known to persist in the polysaccharide chains (cellulose) formed by this disaccharide in the crystalline state, 8,223 and probably represents an important determinant of the physico-chemical and mechanical properties of this material (stability, rigidity, and insolubility in water 224 ).…”
Section: Hydrogen Bondingmentioning
confidence: 47%
“…Virtually no adsorption of glucose and cellotetraose to the cellulose substrate was detected (in line with cellobiose), whereas cellohexaose showed a quite high cellulose affinity (Table). These results appear reasonable because cellohexaose inherently gathers together with time in an aqueous medium owing to its high self-assembling property via unique hydrogen bondings [17]. The number of the β-1,4-glucan units would therefore be a critical factor affecting the cellulosebinding ability of polymers containing cellooligosaccharides such as CB-A-PAM.…”
Section: Affinity Of Cb-a-pam For Cellulosementioning
confidence: 87%